Determination of Islamic Capital Structure: A Literature Review - Muhammad Anwar Fathoni; Tasya Hadi Syahputri (ITB AAS INDONESIA Surakarta, 2021)
This study aims to examine the capital structure in Islamic economics, in terms of components, characteristics and factors that affect the capital structure. This research is a literature study that used a descriptive-qualitative approach. The data used in this research is secondary data. The results show that the decision to formulate the capital structure must be made appropriately so that the company avoids various risks. The capital structure in Islam prohibits the elements of Maysir, Gharar, Riba in it. In general, the factors that influence the capital structure are liquidity, profitability, sales growth and asset structure. However, it all returns to the types and characteristics of the company and the company's management decisions.